Recorrência no tratamento cirúrgico da atresia coanal congênita - Cedin, Antonio Carlos [UNIFESP] (2010)
Since the first report of surgical treatment, in the middle of the XIX century, different techniques and approaches have been described. However, there is still no consensus in the literature as to the ideal technique for managing this malformation. The main complication of surgeries for treatment of this malformation is choanal restenosis. The statistics of the indexes of restenosis vary in the literature from 9% to 36%, with an average of 4-6 re-operations per patient. The main surgical techniques use transnasal (endoscopic and microscopic) and transpalatal approaches. The choice between transnasal and transpalatine approaches and also whether to use stents or not in the postoperative period still remains controversial in the surgical management of choanal atresia. We previously described a new endoscopic technique for surgical correction of choanal atresia that eliminates the use of nasal stents or packing. The transeptal endoscopic approach we proposed and used in our series of 21 patients makes it possible to fashion flaps from the septal, nasal and pharyngeal mucosa of the atretic plates in order to cover the raw areas. These flaps were fixed with fibrin glue, dispensing with the need to use stents or nasal packing in all cases in this series. Excessive scar tissue, which is a frequent cause of synechia, was not observed, perhaps because there were practically no areas without mucosal flap protection. Due to conflicting data in the current literature, regarding the best surgical options, evidence is sought to orient decision making in choosing the best surgical technique for the treatment of congenital choanal atresia that will result in lower rates of restenosis. For this objective, we analised a serie of 21 pacients operated on using our technique with a follow up from 6 months to 10 years. These results were analyzed in comparison with those of other authors, selected by a systematic review of the literature. A statistical analysis was done with the objective of determining if the use of flaps fashioned from mucosa, as part of the surgical correction, diminished the number of recurrences. The statistical analysis showed that the possibility of failure of the flap techniques was 9.25% compared to 30.02% of those that did not use them. The success rate with the use of flaps was 90.75% compared to 69.98% without the use of flaps. The odds ratio of 0.2376 (IC95%[0.1370;0.4120]) confirmed that the chance of surgical failure of techniques with the use of flaps was 23.76% of that of the risk to those without the use of flaps. There is a statistical significance between low rates of failures and use of the flaps.These results should be interpreted considering the limitations in the quality of the studies due to the lack of availability of controlled, randomized and blind trials, as would be normally required for more valid statistical evidence. However, we can consider that they corroborate a general impression from different authors, which show that the use of mucosal flaps provides more successful surgery in the treatment of congenital choanal atresia.